1998
DOI: 10.1046/j.1365-2958.1998.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein translocation into host epithelial cells by infecting enteropathogenic Escherichia coli

Abstract: SummaryEnteropathogenic Escherichia coli (EPEC) causes diarrhoea in young children. EPEC induces the formation of actin pedestal in infected epithelial cells. A type III protein secretion system and several proteins that are secreted by this system, including EspB, are involved in inducing the formation of the actin pedestals. We have demonstrated that contact of EPEC with HeLa cells is associated with the induction of production and secretion of EspB. Shortly after infection, EPEC initiates translocation of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
140
2
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(148 citation statements)
references
References 35 publications
5
140
2
1
Order By: Relevance
“…S1A). We also found that the levels of EspB effector, a component of the translocation pore, 36 were not diminished in Nckdeficient cells, as observed with EspF (Fig. S1A).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…S1A). We also found that the levels of EspB effector, a component of the translocation pore, 36 were not diminished in Nckdeficient cells, as observed with EspF (Fig. S1A).…”
Section: Resultssupporting
confidence: 68%
“…37 Moreover, the levels of Tir and that of other effectors detected in the insoluble fraction are an indicator of bacterial attachment to cells. 36 We found that the levels of DnaK in the insoluble fraction of Nck-deficient cells were decreased with respect to control cells (asterisk in Fig. S1B).…”
Section: Resultsmentioning
confidence: 85%
“…115 This filament functions in initial attachment to the host cell before secretion of the translocators, EspB and EspD, which form the translocation pore in the host cell membrane. 116,117 EHEC and EPEC use the T3SS to inject dozens of effector proteins into the eukaryotic cell cytoplasm. Once translocated, these effector proteins are targeted to different subcellular compartments and affect diverse signaling pathways and physiological processes.…”
mentioning
confidence: 99%
“…It is generally assumed that after initial attachment of EPEC and STEC to the intestinal epithelium, a LEE-encoded type III-secreted protein translocation tube is formed, which connects the pathogen with its target cell (15,16). EspA seems to be a major component of this tube (17,18), whereas EspD (19,20) and EspB (18,21,22) appear to be inserted into the host membrane, forming a pore structure. Thus, additional Esp proteins such as EspE/translocated intimin receptor (23,24) and EspF (25) can be directly injected from the cytoplasm of the bacterium into the host cell to modulate host responses.…”
mentioning
confidence: 99%